The cost of 'lost' intimacy. The effect of relationship state on criminal justice decision making - Dawson, Myrna (The British journal of criminology, 2003)
Socio-legal and feminist theorists argue that law varies inversely with relational distance (Black 1976; Rapaport 1991). Relational distance is not static, however, and so law may increase or decrease in tandem with changes in relationships. Similarly, various theoretical perspectives predict that defendants who victimize intimate partners from whom they are estranged will be punished more severely than defendants who victimize current partners. Drawing from this work, I examine whether separation' killings attract harsher sanctions than intact' killings. Using 144 cases of intimate femicide that occurred in Toronto, Canada, my results demonstrate that offenders who kill estranged partners are treated more severely than those who kill current partners. Discussing possible interpretations of this differential legal treatment, I highlight assumptions that may underlie such a punishment rationale, suggesting avenues for future research